Mapping of Mangrove Ecosystem In Segara Anakan Lagoon using Normalized Different Vegetation Index and Dominant Vegetation Index - Hilmi, Endang; Sari, Lilik Kartika; Mahdiana, Arif; Junaidi, Teuku; Muslih, Muslih; Samudra, Sesilia Rani; Prayogo, Norman Arie; Baedowi, Muhamad; Cahyo, Tri Nur; Putra, Rifky Raihady Danu; Sari, Fitra Amalia (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Mangrove ecosystem in Segara Anakan Lagoon (SAL) Cilacap as a typical and specific semiclosed estuary. SAL is dominated by many species like as Rhizophora spp., Sonneratia spp., Bruguiera spp., Avicennia spp., and other species. The normalized different vegetation index (NDVI) and dominant vegetation index (DVI) are a suitable method to support the mapping analysis of mangrove structure and mangrove density. This research aimed to develop mapping of mangrove species distribution, density and dominated species using NDVI and DVI. The method of this research used NDVI analysis using satellite imagery 2017-2020 and domination vegetation with line and quadrat transect method. The results showed that West Segara Anakan had mangrove dense (25 %), moderate density (25 %), rare density (50%) and East Segara Anakan had mangrove dense (43,86 %), moderate density (47.99 %), rare density (8,24 %). Based on domination species showed that East Segara Anakan was dominated by Rhizophora stylosa (233-1633 trees ha-1), Rhizophora apiculata (100-1067 trees ha-1), Nypa frutican (50-2775 trees ha-1), whereas West Segara Anakan was dominated by Nypa frutican (565-2333 trees ha-1), Avicennia marina (198-933 trees ha-1), Sonneratia caseolaris (132-700 trees ha-1) and Avicennia alba (107-1000 trees ha-1). Keywords : Mangrove density, mapping analysis, Segara Anakan Lagoon, NDVI and NDWI